2016
DOI: 10.1016/j.jmaa.2015.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of periodic diffusion with small jumps

Abstract: In this paper, we study the homogenization of a diffusion process with jumps, that is, Feller process generated by an integro-differential operator. This problem is closely related to the problem of homogenization of boundary value problems arising in studying the behavior of heterogeneous media. Under the assumptions that the corresponding generator has vanishing drift coefficient, rapidly periodically oscillating diffusion and jump coefficients, that it admits only "small jumps" (that is, the jump kernel has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…limit equation. Since one can approximate diffusions through much simpler objects such as random walks or Markov chains, it is not surprising that there are also homogenization models for jump processes that generate a diffusion in the limit, see [San16] or [PZ17], An annealed convergence result for jump processes in random media is contained in [RV09, Theorem 5.3]. As in our quenched result, no corrector appears.…”
Section: Introductionmentioning
confidence: 82%
“…limit equation. Since one can approximate diffusions through much simpler objects such as random walks or Markov chains, it is not surprising that there are also homogenization models for jump processes that generate a diffusion in the limit, see [San16] or [PZ17], An annealed convergence result for jump processes in random media is contained in [RV09, Theorem 5.3]. As in our quenched result, no corrector appears.…”
Section: Introductionmentioning
confidence: 82%
“…The methods used in the these papers are analytic and called the corrector method. The probabilistic study of homogenization of periodic stable-like processes can be found in [20,25,37] via the characteristics of semimartingales, in [21,23,24] by SDE driven by Lévy processes or by Poisson random measures, and in [22,41] via the martingale problem method. A closely related topic is homogenization of non-local operators or jump diffusions in random media, which typically requires a different approach than the periodic media case, see [36,40] for example.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a non-local linear operator with a kernel of convolution type in periodic medium [25], concerning certain diffusion process with jumps have been considered. That is also known Feller process generated by an integro-differential operator [30]. Homogenization of a certain class of integrodifferential equations with Lévy operators [3], including scaling limits for symmetric Itô-Lévy processes in random medium [26] has been studied.…”
Section: Introductionmentioning
confidence: 99%